Adaptation theory: elements identified in pediatric patients in substitutive kidney therapy (Research, Society and Development, 2020)
Objective: To identify adaptation problems, according to the Theoretical Model proposed by Sister Callista Roy, in children undergoing hemodialysis treatment. Methodology: Cross-sectional and descriptive study, conducted with 16 patients, at a referral center for pediatric renal therapy in a city in northern Brazil. For the collection, an interview form and data collection from medical records were used, from January to March 2016. Results: Regarding hemodialysis data, the duration of therapy varied from 12 to 96 months, with an average of 31.68 months, that is, an average of 2 years and 8 months. The predominant vascular access was the catheter (87.5%). Eleven adaptive problems were identified in ways related to physiological, self-concept, identity and interdependence. Conclusion: the use of Roy's adaptation model was appropriate, as it allowed us to understand the changes related to adaptive modes and to visualize in a concrete way which are the focuses for nursing interventions. Conclusión: el uso del modelo de adaptación de Roy fue apropiado, ya que nos permitió comprender los cambios relacionados con los modos adaptativos y visualizar de manera concreta cuáles son los focos para las intervenciones de enfermería.